Reply for comment on "Exposure to microplastics (<10 μm) associated to plastic bottles mineral water consumption: The first quantitative study by Zuccarello et al. [Water Research 157 (2019) 365–371]". (1st December 2019) - Zuccarello, P.; Ferrante, M.; Cristaldi, A.; Copat, C.; Grasso, A.; Sangregorio, D.; Fiore, M.; Oliveri Conti, G.
Abstract: Microplastics (MPs) are a threat to both the environment and human health. In the absence of an official method that would allow the analysis of all MPs with diameters less than 10 μm, it was not possible to estimate the exact exposure to these contaminants, yet. In the last years, few studies are available in literature with the first data concerning the concentrations of MPs on bottle mineral waters. Zuccarello et al. (2019) carried out an exposure assessment study where a high value of EDI (Estimated Daily Intake) has been reported. This rebuttal letter aims to reply to the comments of Oßmann et al. (2018) on the article of Zuccarello et al. (2019) about the new analytical method and both the use and the interpretation of Principal Component Analysis.